Pemberdayaan dan Pemaksimalan LAZISMU Medan sebagai Upaya Menghimpun, Menyalurkan, dan Melaporkan melalui Digital Donation Application - Feza Ihram Syahri; Indra Purwanto; Rahmat Veriyadna; Lusi Puspita Sari; Widya Widya; Muhammad Shareza Hafiz (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2020)
The aim in implementing this service is to empower and maximize the Medan City Amil Zakat, Infaq, and Shadaqoh Muhammadiyah Institution (LazisMU) as an effort to collect, distribute and report Zakat, Infaq, and Shadaqoh funds. The scope of service includes the Medan City Amil Zakat, Infaq and Shadaqah Muhammadiyah Institution (LAZISMU) which is a non-profit partner that has experienced several obstacles in carrying out its functions, namely: collecting Zakat, Infaq, and Sadaqah (ZIS) funds and the search for donors is still in a way manual so that sometimes donors do not easily believe, difficulties in following up infaq and sadaqah boxes, many boxes are damaged or even lost, people still doubt that the funds donated did not reach LazisMu Medan City and were distributed on target, and reporting was still only done in the monthly LazisMU Medan City bulletin. The method of implementation is carried out by reviewing documents, observing, and conducting interviews as an initial stage in gathering information. Furthermore, the implementation which is carried out online starts from Training Need Analysis, counseling, training, mentoring and evaluation. This service program has succeeded in minimizing partner problems and providing benefits to partners which are proven qualitatively through direct in-depth interviews via zoom and video testimonials. Meanwhile, quantitatively it can be concluded that 35% said it was useful and 65% said it was very useful.